Epistemes - other: potential contribution to intercultural health organization in Colombia - Portela Guarín, Hugo (Universidad y Salud, 2014)
The reflection article reports that the Health System in Colombia, due to its operations under the standards of the law 100 of 1993, did not do relevant previsions to guarantee the accomplishment of the law, and it was limited to the imposition of a unique model that does not recognize the Colombian sociocultural diversity with its epistemes and heterogeneous healing practices that have remained on time, despite the variety of strategies that have tried to eliminate them. There are 87 indigenous people from this resistance experience who have survived, thanks to their abilities and cultural principles, by constructing the present constantly and not conjectural in contexts of change and transformation, where the permanence of "archaic elements" is not exactly what defines their ethnicities. If the epistemes-others were recognized, they could contribute to the organization of health in an intercultural perspective and public service to strengthen the territories, governments and indigenous cultures.